2006
DOI: 10.1111/j.1540-8167.2006.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Slow Pathway Conduction After Successful AVNRT Ablation

Abstract: Ablation, which successfully eliminates inducible and spontaneous AVNRT in the presence of persistent slow pathway conduction, is associated with significantly altered slow pathway conduction characteristics, indicating the presence of a damaged or different slow pathway after ablation, incapable of sustaining tachycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…Recently, Posan et al [29] showed that in patients with persistent slow pathway conduction after RF ablation, but no recurrent AVNRT, slow pathway ERP increased, while the difference between the fast and slow pathway ERP was reduced, thus decreasing the induction window of reentry [30]. The same operating mechanism could be extrapolated to cryoablation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Posan et al [29] showed that in patients with persistent slow pathway conduction after RF ablation, but no recurrent AVNRT, slow pathway ERP increased, while the difference between the fast and slow pathway ERP was reduced, thus decreasing the induction window of reentry [30]. The same operating mechanism could be extrapolated to cryoablation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Posan et al demonstrated that in patients with persistent slow pathway conduction, but no recurrent AVNRT, a number of conduction property modifications occur. Slow pathway effective refractory periods increase, while the maximum slow pathway atrial‐His (AH) interval, the range of slow pathway AH intervals, and the difference between the fast and slow pathway effective refractory periods are all reduced 16 . This occurs without a significant change in the slow pathway functional refractory period.…”
Section: Discussionmentioning
confidence: 99%
“…Slow pathway effective refractory periods increase, while the maximum slow pathway atrial-His (AH) interval, the range of slow pathway AH intervals, and the difference between the fast and slow pathway effective refractory periods are all reduced. 16 This occurs without a significant change in the slow pathway functional refractory period. The authors argue that these changes prevent the induction of AVNRT because either the initial slow pathway can no longer sustain persistent 1:1 A:V conduction or the remaining conduction is via a second slow pathway that again cannot sustain persistent A:V conduction.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of the electrophysiological mechanisms underlying AVNRT has remained generally unchanged for many years 2,3 and the exact anatomical correlates of the mechanism remain a mystery 4 . Persistence of slow pathway conduction after ablation has been well‐documented after successful elimination of tachycardia 5–9 .…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of the electrophysiological mechanisms underlying AVNRT has remained generally unchanged for many years 2,3 and the exact anatomical correlates of the mechanism remain a mystery. 4 Persistence of slow pathway conduction after ablation has been well-documented after successful elimination of tachycardia. [5][6][7][8][9] This case is consistent with previous evidence that elimination of slow pathway conduction is not necessary for successful AVNRT ablation.…”
Section: Discussionmentioning
confidence: 99%